HUBUNGAN INTENSITAS PENGGUNAAN INSTAGRAM STORY DENGAN INTERAKSI SOSIAL MAHASISWA KOMUNIKASI DIGITAL DAN MEDIA SEKOLAH VOKASI IPB UNIVERSITY - Aureliahermansyah, Nazwa; Wahyu Budi Priatna; Rici Tri Harpin Pranata; Sutisna Riyanto (Jurnal Netnografi Komunikasi, 2026)
The development of social media has changed communication patterns and social interactions among university students, particularly through interactive visual features such as Instagram Story. This feature allows users to share temporary content and encourages responses and engagement in computer-mediated communication. High intensity of Instagram Story usage is assumed to increase opportunities for social interaction among users. This study aims to examine the relationship between the intensity of Instagram Story usage and social interaction among students of the Digital Communication and Media Program, Vocational School, IPB University. The research employed a quantitative approach with a correlational survey design. The population consisted of 319 active students from the 60th cohort, with 77 respondents selected using simple random sampling. Data were collected through an online questionnaire using a five-point Likert scale. The intensity of Instagram Story usage was measured through frequency, duration, and attention, while social interaction was assessed using indicators of responsiveness, engagement, and continuity of interaction. Data analysis was conducted using the Spearman Rank correlation test due to non-normal data distribution. The results show a positive relationship with a moderate level of strength between Instagram Story usage intensity and students’ social interaction (r = 0.458; p < 0.05). These findings indicate that higher intensity of Instagram Story usage is associated with increased social interaction. This study supports Social Information Processing Theory, which explains that social interaction in digital communication develops through continuous message exchanges over time.